Connected and disrupted hydrosocial territories: the making of modern socionatures through inter-basin water transfers - Nick Bourguignon (Journal of Political Ecology, 2023)
Actual and projected water scarcity has accelerated the scale of hydrological infrastructure and the number of Inter-Basin Water Transfers (IBWTs), which move freshwater from one geographically distinct river catchment or basin to another. IBWTs are supply-side programs that pose distinct water governance challenges. If all projected IBWTs are completed by 2050, the volume of water transferred would be 48% of global water withdrawals. This article examines IBWTs from a socionatural perspective. Building on the political ecology scholarship of hydrosocial territories, I probe how IWBTs co-constitute and reconfigure socionatural relations, and how these are experienced by communities and ecologies in unequal ways. I discuss how IBWTs bring about changes, what features of hydrosocial territories they influence, and what conflicts emerge. For 29 IBWTs I define their multiple socionatural dimensions – biophysical, socioeconomic and governance – and the interrelations between them. IBWTs generally degrade biophysical and socioeconomic conditions for communities in water-sending "donor" basins, and condition future territorial reconfigurations. Water governance institutions are ill-equipped to take on the challenge that IBWTs bring in governing across multiple basins, indicated by the conflicts they generate. These concern defense of territory and ways of life, as well as allocation disputes. Political conflicts emerge because worlds shift irrevocably when IBWTs become fixtures of hydrosocial territories.